Congenital syphilis in the Russian Federation: magnitude, determinants, and consequences. Issue 2 (1st April 2003) - Tikhonova, L; Salakhov, E; Southwick, K; Shakarishvili, A; Ryan, C; Hillis, S
Abstract : Objectives: Reported cases of congenital syphilis in the Russian Federation increased 26-fold from 1991–9. Our objectives were to describe the frequency, risk factors, and consequences of delivering an infant with congenital syphilis among pregnant women with active syphilis. Methods: In a retrospective record review using consecutive sampling of logs at maternity hospitals in five geographic areas, data were abstracted for 850 women with active syphilis during pregnancy who had completed ≥20 weeks' gestation. Further information was abstracted from records in antenatal clinics, dermatovenereology clinics, and paediatric hospitals. We assessed the frequency of confirmed or probable congenital syphilis, used logistic modelling to identify independent predictors for delivering a baby with congenital syphilis, and calculated the proportion of infants with congenital syphilis who experienced late fetal death (20–27 weeks), stillbirth (≥28 weeks), or infant death. Results: A total of 64% (n=544) of 850 pregnant syphilis infected women delivered an infant with confirmed or probable congenital syphilis; 40% of the sample had no prenatal care. Among women with no prenatal care, 77% received either no treatment or inadequate treatment and 86% delivered an infant with congenital syphilis. Important independent and modifiable risk factors for delivery of an infant with congenital syphilis included receiving no prenatal care (adjusted OR 2.8, 95% CI 1.7 to 4.7) and having the first test for syphilis at ≥28 weeks' gestation (adjusted OR 4.0, 95% CI 2.6 to 6.0). Fatal outcomes were observed in 26% of infants with congenital syphilis, including late fetal death (7%), stillbirth (16%), or neonatal death (3%). Conclusions: In the Russian Federation, the frequency of congenital syphilis is high, risk factors for congenital syphilis are modifiable, and the consequences of congenital syphilis are severe.